A framework for optimal control of oscillations and synchrony applied to non-linear models of neural population dynamics - Salfenmoser, Lena; Obermayer, Klaus (Frontiers in Computational Neuroscience, 2024)
We adapt nonlinear optimal control theory (OCT) to control oscillations and network synchrony and apply it to models of neural population dynamics. OCT is a mathematical framework to compute an efficient stimulation for dynamical systems. In its standard formulation, it requires a well-defined reference trajectory as target state. This requirement, however, may be overly restrictive for oscillatory targets, where the exact trajectory shape might not be relevant. To overcome this limitation, we introduce three alternative cost functionals to target oscillations and synchrony without specification of a reference trajectory. We successfully apply these cost functionals to single-node and network models of neural populations, in which each node is described by either the Wilson-Cowan model or a biophysically realistic high-dimensional meanfield model of exponential integrate-and-fire neurons. We compute efficient control strategies for four different control tasks. Firstly, we drive oscillations from a stable stationary state at a particular frequency. Secondly, we switch between stationary and oscillatory stable states and find a translational invariance of the state-switching control signals. Thirdly, we switch between in-phase and out-of-phase oscillations in a two-node network, where all cost functionals lead to identical OC signals in the minimum-energy limit. Finally, we (de-) synchronize an (a-) synchronously oscillating six-node network. In this setup, for the desynchronization task, we find very different control strategies for the three cost functionals. The suggested methods represent a toolbox that enables to include oscillatory phenomena into the framework of nonlinear OCT without specification of an exact reference trajectory. However, task-specific adjustments of the optimization parameters have to be performed in order to obtain informative results.